Fuel Cells for Transportation - Fundamental Principles and Applications - Das, Prodip K; Jiao, Kui; Wang, Yun; Barbir, Frano; Li, Xianguo (Elsevier, 2023)
This book is the first comprehensive reference on the application of fuel cells for light- and heavy-duty transportation. Addressing the subject from both a materials and engineering perspective, the book examines integration, modeling, and optimization of fuel cells from fundamentals to the latest advances. Chapters address every aspect of fuel cell systems for transport applications, including performance optimization, stack characterization, low-cost materials and catalysts, design of bipolar plates and flow fields, water and thermal management, durability under automotive driving cycles, cold start, state of the art characterization, optimization of various components, and more.Each chapter reviews the fundamental principles of the topic before going on to examine the latest developments alongside current applications and real-world case studies. This is an essential reference for graduate students and researchers working on fuel cells for transport applications, as well as professional engineers involved in the application of fuel cells and clean energy and working in any sector of the transportation industry.